Preparation method and application of topological star-shaped nano hollow reactor

By controlling the mass ratio of Zn(NO3)2·6H2O and 2-methylimidazole, and using tannin etchant, a star-shaped ZIF-8 nanocolumn material was prepared, which solved the problems of single topological structure and harsh template removal conditions in traditional MOF-derived nanohollow reactors, and achieved the preparation of a high-symmetric star-shaped nanohollow reactor with higher technical effects.

CN119684623AActive Publication Date: 2025-03-25HARBIN INSTITUTE OF TECHNOLOGY (SHENZHEN) (INSTITUTE OF SCIENCE AND TECHNOLOGY INNOVATION HARBIN INSTITUTE OF TECHNOLOGY SHENZHEN)
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411870236.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The geometric topology of traditional MOF-derived nano-hollow reactors is usually cubes or prismatic dodecahedrons. The formation of hollow topology requires template assistance, and the conditions for removing templates are harsh.

Method used

Star ZIF-8 nanocolumn material was successfully prepared by controlling the mass ratio of Zn(NO3)2·6H2O and 2-methylimidazole and adding cetyl trimethylammonium bromide (CTAB) as the surfactant. Then, a hollow topological structure is formed using tannin as an etchant, and a core-shell nano-hollow reactor of carbon-based shell/metal-based compound is prepared in one step by in-situ calcination.

Benefits of technology

The preparation of star nano ZIF materials with high symmetry and cross-crossing each other is achieved, avoiding the disadvantages of the template method, and forming a highly discrete hollow topological star structure, with the overall technical effect being better than traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684623A_ABST
    Figure CN119684623A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a topological star-shaped nano hollow reactor, and aims to solve the problems that the formation of a traditional MOF (Metal Organic Framework)-derived nano hollow reactor needs template assistance and the template removal condition is harsh. The preparation method comprises the following steps: 1, mixing zinc nitrate and CTAB (cetyltrimethyl ammonium bromide), and dissolving in deionized water to obtain a zinc nitrate solution; the preparation method comprises the following steps: adding 2-methylimidazole into deionized water, stirring to obtain a methylimidazole solution, and adding the methylimidazole solution into a zinc nitrate solution to react to obtain a star-shaped ZIF-8 nanorod material; 2, a tannic acid aqueous solution is added into the star-shaped ZIF-8 nanorod material dispersion liquid, and a star-shaped hollow ZIF-8 nanorod material is obtained; and 3, calcining to obtain the topological star-shaped nano hollow reactor. According to the method, effective regulation and control of the geometric topological structure of the MOF-based material are achieved through simple and mild chemical means, the hollow structure is etched through organic acid, and complexity of a template removal step in traditional etching is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a MOF-derived hollow nano material. Background Art

[0002] Metal organic framework compounds (MOFs) can be used as precursors or templates to fabricate MOF-derived hollow nanoreactors (HoNRs). They are often composed of metal compounds, layered double hydroxides, bioenzymes and their hybrid composites. MOF-derived hollow nanoreactors play an important role in photocatalysis, energy storage and conversion, and biomedicine because of their superior properties, such as large specific surface area, micropores or mesopores, efficient electron and mass transport during the reaction, inherited structural versatility, high tolerance to acidic and alkaline environments, electrical conductivity, and diversity of chemical composition.

[0003] In most cases, the technical synthesis routes of MOF-derived nano hollow reactors mainly rely on the decomposition of MOF or its composites under certain conditions or chemical reactions with ideal reagents:

[0004] (1) Hollow silica derived from the minor components of MOF@shell composites;

[0005] (2) Hollow porous carbon materials derived from the organic components of MOF and its shell molecules;

[0006] (3) Hollow metal oxides, sulfides, carbides, supported HoNRs, etc. derived from the metal components of MOFs or MOF composites.

[0007] The geometric topology of traditional MOF-derived nano hollow reactors is usually a cube or a prismatic dodecahedron. It is difficult to synthesize MOF-based precursors with complex topological structures using simple chemical synthesis. In addition, the formation of hollow topological structures usually requires the assistance of templates, such as silicon dioxide (SiO2) and polystyrene (PS), and the significant disadvantage of this method is that the template can only be removed under harsh conditions. Not only is the cost-effectiveness relatively high, but the entire synthesis process is difficult, and a lot of waste is generated, which does not have the economy and universality for large-scale preparation. Summary of the invention

[0008] The purpose of the present invention is to solve the problem that the geometric topology of traditional MOF-derived nano hollow reactors is usually a cube or a prismatic dodecahedron, the formation of the hollow topological structure requires template assistance, and the conditions for removing the template are harsh, and to provide a method for preparing a topological star-shaped nano hollow reactor.

[0009] The preparation method of the topological star-shaped nano hollow reactor of the present invention is achieved by the following steps:

[0010] 1. Synthesis of star-shaped ZIF-8 nanorods:

[0011] Mix Zn(NO3)2·6H2O and cetyltrimethylammonium bromide (CTAB) and dissolve them in deionized water to obtain a zinc nitrate solution; add 2-methylimidazole (MeIM) to the deionized water, stir and obtain a methylimidazole solution, add the methylimidazole solution (quickly) to the zinc nitrate solution, let it stand at room temperature for reaction, wash and dry to obtain a star-shaped ZIF-8 nanorod material;

[0012] 2. Synthesis of star-shaped hollow topological precursors:

[0013] The star-shaped ZIF-8 nanocolumn material is added to deionized water, and a dispersion is obtained after ultrasonic dispersion. A tannic acid aqueous solution is added to the dispersion, and the mixture is stirred at room temperature for reaction. The solid phase is collected and dried to obtain a star-shaped hollow ZIF-8 nanocolumn material.

[0014] 3. Synthesis of star-shaped hollow nanoreactors:

[0015] The star-shaped hollow ZIF-8 nanorod material and the activated material powder are placed at both ends of a crucible, calcined at a temperature of 620 to 750° C. in an argon environment, and then cooled to obtain a topological star-shaped nano hollow reactor (material);

[0016] wherein in step 1, the mass ratio of Zn(NO3)2·6H2O to 2-methylimidazole is controlled to be (1-1.5):(7-10); the methylimidazole solution is added to the zinc nitrate solution, and the mass percentage of cetyltrimethylammonium bromide (CTAB) in the system is 0.4-0.8wt%;

[0017] In step 2, the mass ratio of the star-shaped ZIF-8 nanorod material to tannic acid is (15-25):1.

[0018] The application of the topological star-shaped nano hollow reactor of the present invention is to use the topological star-shaped nano hollow reactor as a photocatalytic material, an electrocatalytic material or a drug delivery material.

[0019] The present invention uses the representative zeolitic imidazolate framework structure (ZIF) material in the MOF family as the starting point, and adjusts the amount of surfactant hexadecyltrimethylammonium bromide (CTAB) used in the initial precursor ZIF material, as well as the ratio of metal salt to 2-methylimidazole (2-MeIM) in the synthesis process of the ZIF material. A highly symmetrical, cross-shaped star-shaped nano ZIF material that is different from the traditional geometric topological structure was successfully prepared. On this basis, the present invention uses tannic acid (TA), an organic acid, which is a polyphenol. When tannic acid forms a chelate with the metal sites on MOFs, it can provide many phenolic hydroxyl groups on the surface of MOFs and play a buffering role in an alkaline environment. At the same time, TA macromolecules can chelate on MOFs to form a protective layer to protect the large framework of MOFs from being destroyed. TA slowly releases H + It can anisotropically and uniformly pass through the pores on the surface of the MOF-based material and enter the interior to undergo a mild chemical reaction, thereby avoiding the shortcomings of the "template method" and forming a highly discrete hollow topological star structure. After forming a MOF-based hollow topological structure precursor, at a temperature lower than the evaporation temperature of the metal salt, a core-shell nano hollow reactor of a carbon-based shell / metal-based compound can be prepared in one step by in-situ calcination.

[0020] The present invention realizes effective regulation of the geometric topological structure of MOF-based materials through simple and mild chemical means. And with the help of the etching effect of TA, an organic acid, a highly discrete hollow topological structure is formed. The overall technical effect is better than the nano hollow structure prepared by the traditional "template method". In addition, through calcination or further chemical reaction means, the free metal salt ions in MOF can be converted into corresponding metal compounds in situ. Through the protection mechanism of TA, the stable existence of enzymes and macromolecules in the hollow cavity can also be achieved. This topological hollow structure technology can be expanded to (photo) electrocatalysis, new energy conversion and storage, and biomedicine. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a SEM image of the star-shaped ZIF-8 nanorod prepared in step 1 of Example;

[0022] Figure 2 TEM image of the star-shaped ZIF-8 nanorod prepared in step 1 of Example;

[0023] Figure 3 This is a SEM image of the star-shaped hollow topological precursor prepared in step 2 of Example;

[0024] Figure 4 This is a SEM image of the topological star-shaped nano hollow reactor prepared in step 3 of the embodiment;

[0025] Figure 5TEM image of the topological star-shaped nano hollow reactor prepared in step 3 of the embodiment;

[0026] Figure 6 The BET diagram (left) and pore volume diagram (right) of the topological star-shaped nano hollow reactor prepared in step 3 of Example;

[0027] Figure 7 The photocatalytic CO2 reduction performance diagram (left figure) and the cyclic stability bar graph (right figure) of the topological star-shaped nano hollow reactor prepared in step three of Example 3. DETAILED DESCRIPTION

[0028] Specific implementation method 1: The preparation method of the topological star-shaped nano hollow reactor in this implementation method is implemented according to the following steps:

[0029] 1. Synthesis of star-shaped ZIF-8 nanorods:

[0030] Mix Zn(NO3)2·6H2O and cetyltrimethylammonium bromide (CTAB) and dissolve them in deionized water to obtain a zinc nitrate solution; add 2-methylimidazole (MeIM) to the deionized water, stir and obtain a methylimidazole solution, add the methylimidazole solution (quickly) to the zinc nitrate solution, let it stand at room temperature to react, wash and dry to obtain a star-shaped ZIF-8 nanocolumn material;

[0031] 2. Synthesis of star-shaped hollow topological precursors:

[0032] The star-shaped ZIF-8 nanocolumn material is added to deionized water, and a dispersion is obtained after ultrasonic dispersion. A tannic acid aqueous solution is added to the dispersion, and the mixture is stirred at room temperature for reaction. The solid phase is collected and dried to obtain a star-shaped hollow ZIF-8 nanocolumn material.

[0033] 3. Synthesis of star-shaped hollow nanoreactors:

[0034] The star-shaped hollow ZIF-8 nanorod material and the activated material powder are placed at both ends of a crucible, calcined at a temperature of 620 to 750° C. in an argon environment, and then cooled to obtain a topological star-shaped nano hollow reactor (material);

[0035] wherein in step 1, the mass ratio of Zn(NO3)2·6H2O to 2-methylimidazole is controlled to be (1-1.5):(7-10); the methylimidazole solution is added to the zinc nitrate solution, and the mass percentage of cetyltrimethylammonium bromide (CTAB) in the system is 0.4-0.8wt%;

[0036] In step 2, the mass ratio of the star-shaped ZIF-8 nanorod material to tannic acid is (15-25):1.

[0037] The preparation method of the topological star-shaped nano hollow reactor in this embodiment includes the following technical features:

[0038] (1) Formation method of novel ZIF-8 structure:

[0039] This embodiment successfully constructs a ZIF-8 structure that is different from the traditional prismatic dodecahedron morphology by controlling the amount of CTAB (cetyltrimethylammonium bromide) and the ratio of Zn ions to 2-methylimidazole in the precursor. This method does not rely on templates and achieves novel structural design by adjusting the concentration and ratio of reactants, which has the advantages of simple synthesis and strong structural controllability.

[0040] (2) Tannic acid etching to construct a hollow cavity structure:

[0041] Tannic acid is used as an etchant to replace the traditional template method to form a hollow cavity structure. This organic acid etching method has the advantages of being green and environmentally friendly, easy to operate, and can more accurately control the morphology and size of the hollow structure, avoiding the complexity of the template removal step in traditional etching.

[0042] (3) In-situ calcination to achieve Zn-based composite semiconductor star-shaped topology HoNRs:

[0043] The hollow cavity structure was further transformed into hollow nanoreactors (HoNRs) with Zn-based composite star-shaped topology with semiconductor properties by in-situ calcination process. This in-situ calcination method not only enhances the electrical properties of the material, but also ensures the stability of the complex topology at high temperature, making it have a wide range of application potentials in catalysis, electrochemistry and optoelectronics.

[0044] Specific embodiment 2: The difference between this embodiment and specific embodiment 1 is that in step 1, 1 to 1.5 g of Zn(NO3)2·6H2O and 0.5 to 2 g of cetyltrimethylammonium bromide (CTAB) are mixed and dissolved in 35 to 50 mL of deionized water to obtain a zinc nitrate solution; 7 to 10 g of 2-methylimidazole (MeIM) is added to 100 to 140 mL of deionized water, and the methylimidazole solution is obtained after stirring.

[0045] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that in step one, the methylimidazole solution is added to the zinc nitrate solution, and the mass percentage of cetyltrimethylammonium bromide (CTAB) in the system is 0.5-0.6wt%.

[0046] Specific implementation method 4: This implementation method is different from one of specific implementation methods 1 to 3 in that the static reaction time at room temperature in step 1 is 1.5 to 3 hours.

[0047] Specific implementation mode 5: This implementation mode is different from any one of specific implementation modes 1 to 4 in that the concentration of the tannic acid aqueous solution in step 2 is 5 mg / mL.

[0048] Specific embodiment 6: The difference between this embodiment and any one of specific embodiments 1 to 5 is that in step 2, the mass ratio of the star-shaped ZIF-8 nanorod material to tannic acid is 20:1.

[0049] Specific implementation method 7: This implementation method is different from specific implementation methods 1 to 6 in that the stirring reaction time at room temperature in step 2 is 20 to 45 minutes.

[0050] Specific embodiment eight: This embodiment is different from any one of specific embodiments one to seven in that the activation material powder in step three is Se powder, sulfur powder or tellurium powder.

[0051] This embodiment uses sulfur powder, tellurium powder, etc. to form zinc-based semiconductor materials such as ZnS and ZnTe. In addition, it is expanded to different metal-based MOF materials.

[0052] Specific embodiment 9: The difference between this embodiment and any one of specific embodiments 1 to 8 is that in step 3, the mass ratio of the star-shaped hollow ZIF-8 nanorod material and the activation material powder is (0.3-0.8):1.

[0053] Specific embodiment ten: This embodiment is different from any one of specific embodiments one to nine in that the calcination treatment time in step three is 1.5 to 3 hours.

[0054] Embodiment: The preparation method of the topological star-shaped nano hollow reactor of this embodiment is implemented according to the following steps:

[0055] 1. Synthesis of star-shaped ZIF-8 nanorods:

[0056] 1.332 g of Zn(NO3)2·6H2O and 1 g of cetyltrimethylammonium bromide (CTAB) were mixed and dissolved in 40 mL of deionized water to obtain a zinc nitrate solution; 8 g of 2-methylimidazole (MeIM) was added to 120 mL of deionized water, and the mixture was stirred vigorously for 3 minutes to obtain a methylimidazole solution, and the methylimidazole solution was (quickly) added to the zinc nitrate solution, and allowed to react at room temperature for 2 hours, and then washed with deionized water and ethanol for several times, collected by centrifugation at 10,000 rpm, and dried in vacuo at 50°C to obtain a star-shaped ZIF-8 nanocolumn material;

[0057] 2. Synthesis of star-shaped hollow topological precursors:

[0058] 200 mg of star-shaped ZIF-8 nanocolumn material was added to 30 mL of deionized water, and a dispersion was obtained after ultrasonic treatment at room temperature for 30 minutes. 2 mL of 5 mg / mL tannic acid aqueous solution was added to the dispersion, and the mixture was stirred at room temperature for 30 minutes. The solid phase was collected and dried at 50° C. to obtain a star-shaped hollow ZIF-8 nanocolumn material (hS-ZIF-8);

[0059] 3. Synthesis of star-shaped hollow nanoreactors:

[0060] 0.4 g of star-shaped hollow ZIF-8 nanocolumn material and 1.0 g of Se powder were placed at both ends of an alumina crucible. In an argon environment, the temperature was raised to 650°C at a heating rate of 2°C / min, and the mixture was calcined at 650°C for 2 hours. After naturally cooling to room temperature, a topological star-shaped nanohollow reactor (hC-ZnSe) was obtained.

[0061] In this embodiment, the crystal growth kinetics is controlled by adjusting the synthesis time. After adding a high content of CTAB (>0.16wt%), the crystal growth of the synthesized ZIF-8 crystals (octagonal plates (OP), cross twins (IT) and nanorods (NR)) is closely related to the synthesis kinetics. For OP crystals, as the synthesis time increases, the lateral size of the crystal increases faster than the crystal thickness, resulting in an increase in the aspect ratio of the OP crystal. The particle size of IT crystals with high symmetry also increases with the extension of the synthesis time. For shape-anisotropic NR crystals, the length increases with the extension of the synthesis time, but the thickness remains almost unchanged. Therefore, the aspect ratio of NR crystals will increase as the reaction proceeds. The crystal growth rate slows down with the addition of CTAB, which may be due to the competitive interaction between the ligand and surfactant (CTAB) and the metal source (zinc ions).

[0062] The high specific surface area of ​​the star-shaped structure of the topological star-shaped nano hollow reactor prepared in this embodiment exposes more active sites, thereby improving the reaction rate and efficiency. The hollow design enhances the overall structural stability and reduces the risk of structural collapse during use. The multi-stage pores can reduce the diffusion resistance of the reactants, promote rapid mass transfer, and improve the overall reaction efficiency. Through precise control of the geometric shape and size, a highly targeted nanoreactor can be designed for efficient catalysis or drug delivery under different reaction conditions, thereby enhancing the reaction selectivity and system performance.

[0063] Depend on Figure 4 It can be seen that the nano hollow reactor prepared in this embodiment has a hollow star-shaped topological structure.

[0064] Application Example: In this example, the prepared topological star-shaped nano hollow reactor is used as a photocatalytic material. The experimental process of photocatalysis is as follows:

[0065] In the CO2 photocatalytic reduction reaction, 10 mg of photocatalytic material, 50 mg of [Ru(bpy)3]Cl2·6H2O (abbreviated as Ru, bpy=2'2-bipyridine), 10 mL of triethanolamine (TEOA), 10 mL of H2O and 30 mL of acetonitrile (MeCN) were added to an airtight glass reactor (capacity 420 mL). The mixed sample was uniformly ultrasonicated for 15 minutes and then placed in the photoreaction system. Before the introduction of light irradiation, the photoreaction system was thoroughly vacuum treated (3 times), and then high-purity CO2 was injected into the inner circulation reactor until the pressure reached 1 atmosphere. Then, high-purity CO2 with a partial pressure of 1 atmosphere was introduced into the reactor. The light source was a 300 W Xe lamp with a 420 nm cutoff filter (Beijing Perfect Light Source Co., Ltd.). The temperature of the reaction system was maintained at 10°C. During the photocatalytic process, the reaction system was vigorously stirred with a magnetic stirrer. After the reaction was completed, the product was quantified using a GC-9790Plus (Zhejiang Fuli Analytical Instrument Co., Ltd.) gas chromatograph.

[0066] like Figure 6 As shown, thanks to the high 140.5m 2 g -1 With a specific surface area of ​​3.78 nm and a pore volume of 3.78 nm that is sufficient to support the passage of small molecules, the CH4 generation rate of the topological star-shaped nano-hollow reactor is as high as 215.5 μmol·g -1 ·h -1 , the electron selectivity is as high as 90%. And it has excellent photocatalytic stability ( Figure 7 ). This performance greatly exceeds that of most reported photocatalysts.

[0067] The topological star-shaped nano hollow reactor prepared in this embodiment shows unique advantages in the fields of catalysis, medicine and new energy.

[0068] (1) Effects in the catalytic field

[0069] The star-shaped hollow topology nanoreactor provides a large surface area and multi-level pore structure, which can significantly improve the exposure rate of active sites and the mass transfer efficiency of reactants in catalytic reactions. This geometric structure reduces diffusion limitations, making it easier for reactants to access active sites and accelerates the reaction rate. In addition, since the topology of the nanoreactor can be precisely controlled, the pore size and shape of the reactor can be adjusted for specific reactions, optimizing catalytic performance and improving the selectivity and stability of the catalyst. Therefore, this nanoreactor has great application potential in environmental catalysis, petroleum refining, fine chemicals and other fields.

[0070] (2) Effects in the medical field

[0071] In the field of medicine, the unique topological structure of star-shaped hollow nanoreactors provides an ideal platform for drug delivery. The hollow structure can not only load larger doses of drugs, but also achieve controlled release of drugs by precisely regulating the geometric structure, thereby improving treatment efficiency and reducing side effects. In addition, the geometric design of this nanoreactor can enhance its biocompatibility and targeting in the body, and achieve efficient delivery to specific tissues or cells through topological structure control. Application scenarios include cutting-edge fields such as tumor targeted therapy, precision drug delivery systems, and immunotherapy.

[0072] (3) Effects in the field of new energy

[0073] Star-shaped hollow topological nanoreactors have significant application prospects in new energy technologies, especially in electrocatalysis and photocatalysis. Its unique topological structure can effectively improve the transmission efficiency of electrons and ions, promote reaction activity, and reduce charge recombination. In energy storage devices such as lithium batteries, fuel cells, and supercapacitors, the star-shaped hollow structure helps to improve the energy density, power density, and cycle stability of electrode materials. In the field of photocatalysis, the topological geometric structure of the nanoreactor helps to enhance light absorption capacity and improve the efficiency of photogenerated carrier separation, thereby improving photocatalytic efficiency. It is suitable for new energy conversion and storage technologies such as solar photocatalytic water splitting to produce hydrogen and carbon dioxide reduction.

[0074] When the present invention extends the star-shaped hollow topological structure nanoreactor to other MOF materials, the following variations can also be considered:

[0075] (1) Metal-oxygen cluster modification: By introducing metal oxygen clusters (such as titanium oxygen clusters, molybdenum oxygen clusters, etc.) on the surface or in the pores of MOF, its catalytic activity or stability can be enhanced while maintaining the hollow structure. This modification technology is more common on MOF materials and is suitable for situations where active sites need to be introduced inside the reactor.

[0076] (2) Alloying and multi-metal doping: heterogeneous structures are constructed by doping with multiple metal ions (such as Co-Zn, Cu-Fe, etc.) to further improve catalytic activity or electron transport performance. This alloying strategy can be applied to different MOF materials to enhance their application in new energy and catalysis fields.

[0077] In general, through the fine design and structural regulation of different MOF materials, the manufacturing method of the star-shaped hollow topological structure nanoreactor has strong versatility and deformation space, and can be optimized and adjusted according to different application requirements, thereby exerting its potential value in multiple fields.

Claims

1. A method for preparing a topological star-shaped nano hollow reactor, characterized in that The preparation method is achieved by the following steps:

1. Synthesis of star-shaped ZIF-8 nanorods: Mix Zn(NO3)2·6H2O and hexadecyltrimethylammonium bromide and dissolve them in deionized water to obtain a zinc nitrate solution; add 2-methylimidazole to the deionized water, stir and obtain a methylimidazole solution; add the methylimidazole solution to the zinc nitrate solution, let it stand at room temperature for reaction, wash and dry and obtain a star-shaped ZIF-8 nanocolumn material; 2. Synthesis of star-shaped hollow topological precursors: The star-shaped ZIF-8 nanocolumn material is added to deionized water, and a dispersion is obtained after ultrasonic dispersion. A tannic acid aqueous solution is added to the dispersion, and the mixture is stirred at room temperature for reaction. The solid phase is collected and dried to obtain a star-shaped hollow ZIF-8 nanocolumn material.

3. Synthesis of star-shaped hollow nanoreactors: The star-shaped hollow ZIF-8 nanorod material and the activated material powder are placed at both ends of a crucible, calcined at 620-750°C in an argon environment, and then cooled to obtain a topological star-shaped nano hollow reactor; wherein in step 1, the mass ratio of Zn(NO3)2·6H2O to 2-methylimidazole is controlled to be (1-1.5):(7-10); the methylimidazole solution is added to the zinc nitrate solution, and the mass percentage of hexadecyltrimethylammonium bromide in the system is 0.4-0.8wt%; In step 2, the mass ratio of the star-shaped ZIF-8 nanorod material to tannic acid is (15-25):

1.

2. The method for preparing the topological star-shaped nano hollow reactor according to claim 1, characterized in that In step 1, 1-1.5 g of Zn(NO3)2·6H2O and 0.5-2 g of hexadecyltrimethylammonium bromide are mixed and dissolved in 35-50 mL of deionized water to obtain a zinc nitrate solution; 7-10 g of 2-methylimidazole is added to 100-140 mL of deionized water, and the mixture is stirred to obtain a methylimidazole solution.

3. The method for preparing the topological star-shaped nano hollow reactor according to claim 1, characterized in that In step 1, the methylimidazole solution is added to the zinc nitrate solution, and the mass percentage of hexadecyltrimethylammonium bromide in the system is 0.5-0.6wt%.

4. The method for preparing the topological star-shaped nano hollow reactor according to claim 1, characterized in that In step 1, the reaction time at room temperature is 1.5 to 3 hours.

5. The method for preparing the topological star-shaped nano hollow reactor according to claim 1, characterized in that In step 2, the mass ratio of the star-shaped ZIF-8 nanorod material to tannic acid is 20:

1.

6. The method for preparing the topological star-shaped nano hollow reactor according to claim 1, characterized in that In step 2, the reaction time is 20 to 45 minutes at room temperature.

7. The method for preparing the topological star-shaped nano hollow reactor according to claim 1, characterized in that The activation material powder described in step 3 is Se powder, sulfur powder or tellurium powder.

8. The method for preparing the topological star-shaped nano hollow reactor according to claim 1, characterized in that In step three, the mass ratio of the star-shaped hollow ZIF-8 nanocolumn material and the activated material powder is (0.3-0.8):

1.

9. The method for preparing the topological star-shaped nano hollow reactor according to claim 1, characterized in that The calcination treatment time in step 3 is 1.5 to 3 hours.

10. Use of the topological star-shaped nano hollow reactor prepared as claimed in claim 1, characterized in that The topological star-shaped nano hollow reactor is used as a photocatalytic material, an electrocatalytic material or a drug delivery material.

Citation Information

Patent Citations

  • Preparation method and application of nitrogen-doped nano ZnS / graphene photocatalytic material

    CN111468164A

  • Hollow mesoporous cubic ZIF-8 nano-carrier as well as preparation method and application thereof

    CN114949254A

  • Synthetic method for in-situ construction of defective ZIF-8 / ZnO ordered macroporous heterostructure material

    CN115945219A

  • Hybrid nano composite material Zn-BTEC-ZIF-8, preparation method thereof, fluorescent probe and detection method

    CN116445156A

  • Preparation of star-shaped ZIF-8 and modified electrode and method for detecting heavy metal cadmium

    CN116751368A